Candida krusei development on turbulent flow regimes: Biofilm formation and efficiency of cleaning and disinfection program - Brugnoni, Lorena Inés (2012)
In food processing lines or in complex equipment such as pumps or valves, microorganisms are exposed to varying hydrodynamic conditions caused by the flow of liquid food, and biofilms are thus grown under a wide distribution of local hydrodynamic strengths. Using an industrially relevant strain of Candida krusei, we demonstrated that biofilms formed on stainless steel for 4 days at Reynolds (Re) numbers ranging from 294,000 to 1.2 x 106 proceeds through three distinct developmental phases. These growth phases transform adherent blastospores to well-defined cellular communities encased in an extracellular matrix and biofilm formation increases when increasing Reynolds number and time. In all growth phases, the morphology of C. krusei biofilm revealed the influence of hydrodynamic drag. Indeed, we study the effect of cleaning and sanitation procedure in the control of turbulent flow-generated biofilm. This procedure involves alkali (NaOH 0.5 %) and sodium hypochlorite (500 ppm). In terms of total biofilm mass, removal decreases with increasing biofilm age. The largest reduction post-treatment (between 57-62%) was observed, to all Reynolds numbers, on 24 h and 48h- old biofilms. Removal was between 39 and 46 % on 72 h-old biofilms and was close to 30 % for all Reynolds numbers on 96 h-old biofilm.